Analisis Preferensi Konsumen dalam Memilih Jasa Bank Syariah Indonesia (BSI) KCP Morotai - Muhdar Muba; Fathy Inat; Indasari Sapsuha (ITB AAS INDONESIA Surakarta, 2023)
This study aims to examine product (X1), office location (X2), and service (X3) variables on consumer preferences (Y) in choosing BSI Morotai services. Using regression analysis method, the results shows that partially, only service variable (X3) has a positive and significant effect on consumer preferences. Whereas product (X1) and environment (X2) variables have no significant effect on consumer preferences. The results also shows that simultaneously all the independent variables (X1, X2, and X3) significantly affect the dependent variable (Y). The implication of this study is that Bank Syariah Indonesia (BSI) KCP Morotai needs to improve their communication in line with the customs/culture of local community, while still maintain convenience and prompt service.